Performance Of The Population And Civil Registry Service In Improving The Accuracy Of Translation Level On Temporary Residential Cards (SKTT) At The Department Of Population And Civil Registration Of Sleman Regency, Yogyakarta Special Region Province - Puri Eliviana; Dimas Adika (Registratie, 2025)
For a government institution, legal products issued, for example, population documents, such as the Limited Stay Certificate (SKTT), must be of the highest quality and legally accountable. In this case, the quality I'm referring to is the accuracy of the translation of the limited stay certificate document at the Population and Civil Registration Office of Sleman Regency, Yogyakarta Special Region Province. This research is a qualitative research based on the opinions of the community who use the Limited Stay Certificate service at the Population and Civil Registration Service of Sleman Regency, Special Region of Yogyakarta Province. This research aims to evaluate the accuracy of translations in official Indonesian documents, specifically temporary residential cards (SKTT), using independents sample T test methods (compares the means of two different or unrelated groups), a quantitative approach was used, with data collected through a scale-based questionnaire distributed to professional translators and users of official documents to measure the accuracy level of each translation element. Based of this research results indicate that SKTT get average values 3,9, on a scale from 1 to 5 and T table result Ho is accepted, which means that respondents think that the translation in the SKTT (temporary residential cards) is accurate. Significant factors impacting translation accuracy include the complexity of the original text and translator familiarity with legal terminology. Based on these findings, this study recommends specific improvements in translation practices, particularly focusing on consistency and cultural adaptation. This research is expected to provide valuable insights for translators and institutions to improve the quality of official document translations in Indonesia specifically in Department of population and civil registration of Sleman Regency, Yogyakarta Special Region.